Temporal Analysis of Rainfall Characteristics in Response to Climate Change in the Special Region of Yogyakarta Province - Mashuri, Imawan; Fadhli Aslama Afghani,; Ofana Tri Wibowo, (JFT: Jurnal Fisika dan Terapannya, 2025)
Climate change has resulted in uneven rainfall variations. The temporal analysis of rainfall in the Special Region of Yogyakarta Province was conducted through the calculation of monthly averages, seasonal averages, and annual trends using the Climate Data Operator (CDO) and Microsoft Excel application over 60 years from 1961 to 2020, utilizing ERA5 data. The time frame is divided into two periods: 1961-1990 and 1991-2020, aiming to observe rainfall characteristics such as changes, patterns, and trends that occurred during these intervals. The highest monthly average rainfall occurs in January for both periods, registering 378 mm for 1961-1990 and 370 mm for 1990-2020. In contrast, the lowest monthly average occurs in August, with values of 51 mm for 1961-1990 and 38 mm for 1991-2020. The highest seasonal average rainfall occurs during the DJF period, with values of 945 mm for 1961-1990 and 1022 mm for 1991-2020. However, the lowest seasonal average occurs during the JJA period, with values of 228 mm for 1961-1990 and 191 mm for 1991-2020. The rainfall trend shows an increase for the first period (1961-1990), whereas decreases in the second period (1991-2020), including wet seasons, dry seasons, and annual. The result can be associated with climate change, where there are occurrences of extremely wet and extremely dry seasons. Overall, the Special Region of Yogyakarta province experienced continuous yearly rainfall from 1961 to 2020.